Research advances in composition, structure and mechanisms of microwave absorbing materials. (1st November 2021) - Pang, Huifang; Duan, Yuping; Huang, Lingxi; Song, Lulu; Liu, Jia; Zhang, Tuo; Yang, Xuan; Liu, Jiangyong; Ma, Xinran; Di, Jingru; Liu, Xiaoji
Abstract: The earliest microwave absorbing materials (MAMs) are fabricated in the early 20th century for military purpose to inhibit radar detection. Currently, the application of MAMs has been existing in every part of human's life to prevent radiation and interference. The microwave absorbant and microwave absorbing coatings classified by composition including alloys, metal oxides, conductive polymers, carbon materials, ceramic materials both in traditional and innovative forms are introduced in this work. Considering the harsh and complex application environment, MAMs with high temperature resistance and infrared-compatible stealth performance are involved. Metamaterials, showing excellent electromagnetic properties which are far beyond that of the materials can achieve, including perfect absorber, digitally coded control metamaterials, bionic structural materials, and adjustable smart metamaterials, are also introduced specifically in this work. In addition, to investigate electromagnetic response of absorbant, the first-principles calculations works are overviewed. The electromagnetic properties, loss mechanisms, structure, fabrication method, regulation approaches, designing principles, current applications, and future prospects of MAMs are involved in this work. This work gives a comprehensively overview over the MAMs for their theoretical and experimental advances in recent years including the military radar (frequency range of 2–18 GHz) stealth materials, relevant infrared compatible (infrared-visible, infrared-radar, infrared-laser) stealth materials, and other stealth materials with multifrequency adaptability.